2007
DOI: 10.3171/spi.2007.6.2.121
|View full text |Cite
|
Sign up to set email alerts
|

Serum creatine phosphokinase activity and histological changes in the multifidus muscle: a prospective randomized controlled comparative study of discectomy with or without retraction

Abstract: Object The aim of this study was to determine the extent of muscle injury caused by continuous or intermittent muscle retraction during macro- and microdiscectomy in lumbar disc surgery. Pain scores, serum creatine phosphokinase (CPK) levels, and histological findings obtained in muscle specimens were compared. Methods Sixty patients who underwent surgery for a one-level disc herniation during a 1-year p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 26 publications
1
39
1
1
Order By: Relevance
“…It seems to be true that after a certain time period a smaller skin incision does not inevitably lead to less pain. This is confirmed by a recent study comparing discectomy with or without a retraction system [19].…”
Section: Discussionsupporting
confidence: 72%
“…It seems to be true that after a certain time period a smaller skin incision does not inevitably lead to less pain. This is confirmed by a recent study comparing discectomy with or without a retraction system [19].…”
Section: Discussionsupporting
confidence: 72%
“…In humans, both CRP and CK have been employed in attempts to quantitatively compare the degree of tissue trauma between different surgical techniques 6,17,18 . CK has also been used to evaluate the extent and cause of muscle damage resulting from lumbar back surgery 19,20,22 .…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, other research has reported LM muscle atrophy and injury following lumbar disc surgery, although this appears to vary with surgical approach 53,64,98 and the amount of intraoperative retraction time. 14,28,59,70 Moreover, such changes may be related to the development of failed back syndrome or postdiscectomy syndrome. 95,117 The transversus abdominis (TrA) is another muscle considered to be an important contributor to lumbar spine stability.…”
mentioning
confidence: 99%